Semantic Relations for Interpreting DNA Microarray Data - Hristovski, Dimitar (American Medical Informatics Association, 2009)
The results from microarray experiments, in the form of lists of over- and under-expressed genes, have great potential to support progress in biomedical research. However, results are not easy to interpret. Information about the function of the genes and their relation to other genes is needed, and this information is usually present in vast amounts of biomedical literature. Considerable effort is required to find, read and extract relevant information from the literature. A potential solution is to use computerized text analysis methods to extract relevant information. Our proposal enhances current methods in this regard and uses semantic relations extracted from biomedical text with the SemRep information extraction system. We describe an application that integrates microarray results with semantic relations and discuss its benefits in supporting enhanced access to the relevant literature for interpretation of results.